The Urgency of Social Capital in Local Community Development - Syamsul Bahri; Rusdi Maidin; Asmirah; Iskandar; Nurmi Nonci; Andi Burchanuddin; Harifuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The concept of social capital is widely associated with development, and the term 'development' is always synonymous with changing from an old situation to a new situation with the representation of new values and abandoning old values. This condition is reflected in almost all development that takes place in all corners of the village in Indonesia. The result of such development is physical material progress, but non-material regression such as local socio-cultural values. In this context, this paper is intended to illustrate the urgency of local social capital in rural community development. The social setting of this paper is Tapong Village in Maiwa District, Enrekang Regency, South Sulawesi Province. Tapong village has great socio-cultural potential and social capital that needs to be preserved through development programs, especially culture, so that it can become a local asset. This potential is in the form of the Appa Alliri Customary Institution, and various rituals. Both of these assets are local wisdom as well as socio-cultural assets that live on to this day